Tantangan SIMRS dalam Penerapan Rekam Medis Elektronik Berdasarkan Permenkes 24 Tahun 2022: Literature Review - Rabiah Demlinur Putri; Dety Mulyanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The government through the Ministry of Health of the Republic of Indonesia took a big step by issuing Regulation of the Minister of Health Number 24 of 2022 concerning Electronic Medical Records, whereby through this regulation health service facilities start from independent practice locations for doctors, dentists and/or other health workers, health centers, clinics , hospitals, pharmacies, health laboratories, centers and other Health Service Facilities determined by the Minister are required to implement Electronic Medical Records. Of course, this is a big breakthrough considering that currently the implementation of Electronic Medical Records in Indonesia is said to be not going too well and can even be said to be advanced compared to other countries. This is of course directly related to the infrastructure owned by Health Service Facilities in Indonesia. One of the considerations is the readiness of the Electronic System to be used later, both electronic systems prepared by health care facilities themselves to electronic systems prepared by third parties. There are several important things that must be considered by the electronic system to be able to carry out electronic medical records including the registration of the system as an electronic system operator, having minimum capabilities in accordance with Permenkes No. 24 of 2022 and the ability to maintain data security and protection. Some of these things are a challenge for Electronic Systems or Hospital Information Systems to be able to run Electronic Medical Records according to the provisions that have been set. If this cannot be done, it is likely that the system will receive sanctions up to the revocation of the operating permit.